Integrated Multimodal Transportation Dashboard - Ana Zaiat (2014)
At present time there exist various intelligent systems in Transportation area that permit monitoring, control and other relevant functionalities for a given transport means. However, individual solutions for different transport means don't favor multimodal transport management; there are a very few solutions that combine different transport types in one application. Therefore, a need for a multimodal supervision dashboard arouse - a dashboard that would permit to combine transportation systems of different types and that would provide a comprehensive view in order to observe whether all the systems are functional and operating at an acceptable Level of Service (LOS). Since these systems supply services and data of different scope and varied detail and quality levels, the detection of an abnormal functioning of a certain transportation system is a challenge. It requires identification, application, adaptation or creation of metrics for each transportation system functioning. The metrics should be based on the data supplied by the protocols used by the ITSs integrated in the solution. This problem is addressed by the project "Integrated Multimodal Transportation Dashboard" and has as an aim the elaboration of a functional prototype of a tool for the monitoring of multimodal transports.